Innovation Capability Performance through Potential and Realized Absorptive Capacity: an Empirical Study in the West Java Mini Market - Raharso, Sri - (Jurnal Penelitian Ekonomi dan Bisnis, 2021)
This study explores how potential and realized absorptive capacity affects innovation capability. This study aims to empirically examine the path relationship between potential absorptive capacity, realized absorptive capacity, and innovation capability in mini market in West Java, thus enhance our understanding of the mechanism between absorptive capacity and innovation capability. The authors have conducted a survey among employees with a valid response from 597 respondents. Multiple regression was used to assess the research model. The results provide evidence to show that potential and realized absorptive capacity are positively related to innovation capability, but in different proportions, and potential absorptive capacity affects positively to realize absorptive capacity. This study will contribute in an acceptable way to highlight the effects and role of both the potential absorptive capacity and the realized absorptive capacity in their role as independent variables and the results of this in innovation capability in turn as a dependent variable.Keywords: potential absorptive capacity realized absorptive capacity innovation capability